Barriers to Financial Inclusion in Indonesia: A Mixed-Methods Study on Low-Income Households - Lili Sularmi; Fauziah Septiani; Vidya Amalia Rismanty (Universitas Medan Area, 2023)
Lack of trust in financial institutions is a multi-layered issue shaped by individual experiences, community narratives, systemic factors, and the broader social and cultural milieu. It poses a significant barrier to financial inclusion, as trust is the foundation upon which all financial transactions are built. This study provides an in-depth analysis of the factors affecting financial inclusion among low-income households in Indonesia. Employing a mixed-methods approach, the research combines quantitative data from 241 res-pondents with qualitative insights gathered through in-depth interviews. The study finds that education level is significantly correlated with financial inclusion, confirming its critical role as an individual-level factor. Additionally, while geographic proximity to financial institutions does not guarantee higher financial inclu-sion, other accessibility issues such as complex banking procedures and unreliable internet connectivity act as barriers. Cultural norms and lack of trust in financial institutions also emerge as significant hindrances. The findings call for a multifaceted approach to improve financial inclusion, emphasizing the importance of education, refinement of service accessibility, and building community trust.